Identifying service quality gaps between patients and providers in a Native American outpatient clinic - Robert Dorsey; David Claudio; María A. Velázquez; Polly Petersen (BMC, 2022)
Abstract Background Native American communities in Montana reservations have reported low-level satisfaction in health services. This research explored if the services provided at a Blackfeet Indian Reservation outpatient clinic were designed to meet patient expectations. Methods Staff and patient interviews and surveys allowed service expectations to be assessed according to the clinic's ability to meet those expectations. A total of 48 patients and ten staff members (83% of the staff at this clinic) participated in the study voluntarily. Results We found a disconnect between what patients anticipate for care and what staff think they are anticipating. We also found a discontent between what staff believes patients need versus what the patients feel is needed. Conclusions These gaps combine to increase the breach between patient expectations and perceptions of their healthcare services. With better insight that captures what patients are looking for from a service, the potential to meet those needs increases, and patients feel that their voice is respected and valued.